2022
DOI: 10.3389/fcimb.2022.984049
|View full text |Cite
|
Sign up to set email alerts
|

The role of cholesterol in invasion and growth of malaria parasites

Abstract: Malaria parasites are unicellular eukaryotic pathogens that develop through a complex lifecycle involving two hosts, an anopheline mosquito and a vertebrate host. Throughout this lifecycle, the parasite encounters widely differing conditions and survives in distinct ways, from an intracellular lifestyle in the vertebrate host to exclusively extracellular stages in the mosquito. Although the parasite relies on cholesterol for its growth, the parasite has an ambiguous relationship with cholesterol: cholesterol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…Erythrocyte raft domains are thought to be the areas of the membrane that are cholesterol rich and, thus, targets of MβCD ( 52 ). Furthermore, these raft domains are also the points of invasion of Plasmodium ( 56 ). This leads us to believe that B. divergens invasion must differ from that of malaria parasites in either the specific areas of the RBC membrane that the parasite requires for successful invasion or the cholesterol richness of those same membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocyte raft domains are thought to be the areas of the membrane that are cholesterol rich and, thus, targets of MβCD ( 52 ). Furthermore, these raft domains are also the points of invasion of Plasmodium ( 56 ). This leads us to believe that B. divergens invasion must differ from that of malaria parasites in either the specific areas of the RBC membrane that the parasite requires for successful invasion or the cholesterol richness of those same membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the malaria literature suggest that decreases in HDL associated with babesiosis may be directly related to the growth of the parasite. Multiple studies have shown that Plasmodium spp., Apicomplexans protozoa that are closely related to Babesia spp., does not possess the biosynthetic pathway for de novo synthesis of cholesterol and must scavenge this important molecule from host hepatocyte and erythrocyte membranes [22][23][24]. In humans, acute malaria infections are associated with lower LDL and HDL and the total cholesterol [25].…”
Section: Discussionmentioning
confidence: 99%
“…One more typical example of cholesteroldependent infection is malaria [140][141][142][143] . Plasmodium is not capable of de novo biosynthesis of fatty acids and cholesterol and gets them from the vertebral host.…”
Section: The Pathogenesis Of Some Infectious and Non-infectious Disea...mentioning
confidence: 99%
“…Studies of Samuel et al, 2001 143 proved that cholesterol from the erythrocyte plasma membrane rafts is essential for the invasion and growth of P. falciparum and demonstrated the involvement of cholesterol from erythrocyte membrane raft in the protozoan infection, which was blocked following raft cholesterol disruption. Interestingly, plasmodium creates a cholesterol gradient in the erythrocyte, so that cholesterol from the erythrocyte membrane, where the cholesterol concentration is higher, could flow to the parasitiform vacuole membrane and then to the parasite membrane, where the cholesterol concentration is lowest 142 . This gradient is created by the removal of cholesterol from the parasite membrane by protein NCR1, the Niemann-Pick type C1-related protein, the human orthologue of which, the Niemann-Pick Type C1 protein (NPC1), binds cholesterol.…”
Section: The Pathogenesis Of Some Infectious and Non-infectious Disea...mentioning
confidence: 99%